Proses Klaim Produk Director & Officers (D&O) Liability Insurance di Indonesia - Yulial Hikmah (Jurnal Ekonomi Modernisasi, 2019)
D&O (Directors & Officers) liability insurance is a protection of guarantees for Directors and Company officials (the insured) for losses arising from third party claims due to negligence around managerial or operational matters carried out by the insured. This study discusses the process of settling claims for D&O liability insurance products, claim adjustments in compensation calculations, and provisions in policies that are considered adjustments to compensation calculations. This research was conducted by interview, observation and literature study. The claim process begins with claims from third parties to the insured, and must be reported directly to the guarantor (insurance company) as soon as possible. After the report is received by the guarantor, the guarantor will begin to follow up on the claim by conducting a survey of claim investigation and collecting supporting documents needed. Furthermore, the guarantor will make a decision whether the claim submitted by the insured is guaranteed or not based on the provisions of the policy. If the claim is rejected, a rejection notice will be sent. However, if it turns out that the claim is declared guaranteed, a claim approval notice will be sent to subsequently make a claim payment. Adjustment in the calculation of compensation is needed to optimize the amount of compensation issued by the insurance company so that it can be minimized in order to achieve corporate profits.